The Relationship Between Characteristics of Health Workers on Handwashing Behavior - Ossy Wijaya Iriandoko; Djazuly Chalidyanto (Universitas Muhammadiyah Yogyakarta, 2020)
Based on data from PPI Hospital X in Surabaya there are still nosocomial infections. If the incidence of this infection continues to recur, then the hospital's image will be bad and can cause hospital bed occupational rates to decrease. The purpose of this study was to determine the relationship between the characteristics of health workers (level of knowledge, level of education, age, and length of work) with the level of compliance of health workers doing hand washing at the